Free and guided optical beams : International School of Quantum Electronics, Erice Sicily, Italy, 20-27 November 2002 - Martellucci, S.; Santarsiero, Massimo (World Scientific, 2004)
Optical beams are electromagnetic waves that remain essentially concentrated around a mean axis upon free propagation or that are guided by suitable structures. The study of these beams has existed long ago and since then this field has been a focus of active investigation. However, in recent years, the interest on optical beams has further increased, due to the availability of many types of laser sources, characterized by very different properties, as far as their polarization, coherence, spectral content, and spatial distribution are concerned. This book contains lectures presented in the 35.